Kajian Putusan Mahkamah Konstitusi Terkait Presidential Threshold (Studi Putusan Mahkamah Konstitusi Tahun 2017 -2022) - Hasibuan, Ivan Ihza Shobari; Firdaus, Sunny Ummul (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This research aims to determine and analyze the decision of the Constitutional Court in reviewing chapter 222 Undang-Undang.Nomor 7 Tahun 2017 tentang Pemilihan Umum . This research is doctrinal or normative legal research with an analytical-descriptive character. The material collection technique performed by the author is a literature study by collecting legal material consisting of primary legal material and secondary legal material. The legal materials were analyzed using the deductive method. Formally, the Constitutional Court considers political parties and/or political party coalitions directly affected by the threshold requirements for the nomination of the President and Vice-President in the general election to be entitled to request a review of Article 222 of this Electoral Code. Apart from that, the constitutional court essentially takes the view in its decision that the presidential threshold is a means and a way to strengthen the presidential system in Indonesia. On the other hand, the setting of the presidential difficult for some political parties to accept because it restricts the nomination of candidates for president and vice president. In addition, many parties have filed complaints with the Constitutional Court, both individuals and party representatives, demanding the introduction of a threshold that causes violations of the personal political rights of citizens and political parties.